Modeling of Spray Combustion with a Steady Laminar Flamelet Model in an Aeroengine Combustion Chamber Based on OpenFOAM - Yinli Xiao; Zupeng Wang; Zhengxin Lai; Wenyan Song (International Journal of Aerospace Engineering)
The development of high-performance aeroengine combustion chambers strongly depends on the accuracy and reliability of efficient numerical models. In the present work, a reacting solver with a steady laminar flamelet model and spray model has been developed in OpenFOAM and the solver details are presented. The solver is firstly validated by Sandia/ETH-Zurich flames. Furthermore, it is used to simulate nonpremixed kerosene/air spray combustion in an aeroengine combustion chamber with the RANS method. A comparison with available experimental data shows good agreement and validates the capability of the new developed solver in OpenFOAM.